Videla dies. Public emotions as political arguments - Martin, Lucas (Universidad Nacional del Litoral, 2021)
The purpose of this article is to analyze the way Argentina deals with the criminal legacy of the last dictatorship in light of the event of the death of its main doer, Jorge Rafael Videla. In particular, it focuses on the reactions that, from the center of the public scene and on the part of the most authoritative voices on the subject of human rights, were expressed in the language of emotions and offered, at the same time, an ethic, economy and pedagogy of emotions. With the aid of tools taken from the theory of emotions, we distinguish an order with relief in its center, pain below the surface, pride and satisfaction in the radius, and joy, mourning and anger at the margins. On this basis, we find continuities and differences with respect to the dominant judicial scheme in the treatment of criminal legacy.